2021
DOI: 10.26656/fr.2017.5(2).516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave-assisted extraction on bioactive compounds from industrial tomato waste and its antioxidant activity

Abstract: The bioactive compound of tomato waste from industry was microwave-assisted extracted in different conditions including microwave powers of 180, 300 and 450 W and the extraction time of 30, 60 and 90 s. After extraction, the fractionation was performed to separate the hydrophobic fraction (hexane fraction) and hydrophilic fraction (ethanolic fraction). The bioactive compound and its DPPH radical scavenging activity were determined. For the hydrophobic part, the results showed that the microwave power of 300 W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This index number can be used for comparison and decision the suitable conditions. FAM is an evaluation tool for assessment systems in food product application such as for food product quality control [28], for sensory evaluation [29][30][31], and for decision of optimum extraction conditions [23,32].…”
Section: Introductionmentioning
confidence: 99%
“…This index number can be used for comparison and decision the suitable conditions. FAM is an evaluation tool for assessment systems in food product application such as for food product quality control [28], for sensory evaluation [29][30][31], and for decision of optimum extraction conditions [23,32].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, this technique may provide a solution to the use of high temperature or long heat treatment, which can cause the degradation of lycopene. Lasunon et al very recently investigated the effect of MAE on bioactive compounds from industrial tomato waste and the antioxidant activity of the obtained extract [70]. Generally, the efficiency of microwave extraction is affected by the identification of the optimal extraction parameters; therefore, different conditions including microwave powers of 180, 300, and 450 W and extraction times of 30, 60, and 90 s were evaluated using 95% ethanol with a temperature not exceeding 77 • C. According to the authors, the microwave power of 300 W for 60 s provided the highest trans-lycopene and β-carotene recovery (5.74 mg lycopene/100 g and 4.83 mg β-carotene/100 g).…”
Section: Other Extraction Methodsmentioning
confidence: 99%
“…Similarly, according to Lasunon et al, a 300 W microwave force is able to extract 57 mg of lycopene and 48 mg of β-carotene per kg of tomato waste. In fact, authors also demonstrated the high potential antioxidant content obtained from tomato waste powder.…”
Section: Carotenoidsmentioning
confidence: 99%